Toroidal modeling of the effect of resonant q95 on n = 1 error field penetration in EAST - Cheng Ye; You-Wen Sun; Hui-Hui Wang; Yue-Qiang Liu; Jian Xu; Peng-Cheng Xie; Hui Sheng (Nuclear Fusion)
The plasma response to the n = 1 resonant magnetic perturbation in EAST has been systematically investigated using the MARS-F/Q codes, focusing on the roles of q _95 and $β_\mathrm N$ in error field penetration. Here, q _95 refers to the safety factor at 95% poloidal magnetic flux, which is varied within the low- q _95 operational regime ( $q_{95}\in[3, 4]$ ) by adjusting the plasma current. The normalized beta, $β_\mathrm N$ , is increased by modifying the pressure profile, while remaining below the no-wall beta limit. The resonant q _95 effect observed in the linear response not only influences the penetration of edge resonant components but also affects the q _95 -dependence of $m/n = 2/1$ penetration threshold, with neoclassical toroidal viscosity torque identified as the dominant mechanism. Furthermore, increasing $β_\mathrm N$ shifts the resonant q _95 window. Both linear and quasi-linear simulations reveal that a higher $β_\mathrm N$ enhances the influence of resonant q _95 effect on the $m/n = 2/1$ component. The impact of q _95 on the $α_{β_\mathrm N}$ , which represents the scaling index between $m/n = 2/1$ penetration threshold and $β_\mathrm N$ , shows that $α_{β_\mathrm N}$ becomes increasingly negative with rising q _95 . This indicates that the destabilizing effect of β _N on magnetic field penetration becomes more significant at higher q _95 due to enhanced mode coupling. These findings suggest that modestly adjusting q _95 towards weaker resonant regions can improve error field tolerance, which is beneficial for operational scenarios aimed at mitigating the risk of locked modes. Additionally, the capability to prevent locked mode induced by increasing β _N diminishes as q _95 increases.